Factors Related to Symptoms in Patients Suspect Covid-19 in The Public Health Center Kebayoran Baru in March – June 2020 - Tri Wahyuni; Suherman Suherman; Nazarwin Saputra; Istianah Surury (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
The world is undergoing the new pandemic named COVID-19 of early 2020 announced in China and all over the world and infect more than 10 million people in the world (incidence rate 1.3). Indonesia has the number of cases 28.818 per June 04, 2020, with a CFR of 6%, the highest in Southeast Asia. Besides confirming the case, the suspect like ODP, PDP, and OTG should also be monitored. Although the number of cases and suspects in the Kebayoran Baru district is not the highest in South Jakarta, as the center of South Jakarta where many offices and high mobility, and the population is not as much as another district, so the possible transmission of COVID-19 in Kebayoran Baru still high. To find out the relationship between age, sex, comorbid hypertension, diabetes mellitus, and heart disease with the severity of symptoms in COVID-19 suspect of Kebayoran Baru district March – June 2020. The design of this study used cross-sectional secondary data of COVID-19 suspect monitoring in Community Health Center Kebayoran Baru. Analysis with chi-square 0.005. Statistical results of COVID-19 suspects in the Kebayoran Baru district are 44% having symptoms. The research suggests that a significant relationship between age, hypertension comorbid, diabetes mellitus comorbid, and heart disease with the symptoms. While sex has no significant relation with symptoms. The government should have more attention to protect people that having comorbid such as hypertension, diabetes mellitus, or heart disease.